Per- and Poly-fluoroalkyl Substances (PFAS) Exposure and Risk of Kidney, Liver, and Testicular Cancers: A Systematic Review and Meta-Analysis - Seyyedsalehi, Monireh Sadat; Boffetta, Paolo (La Medicina del Lavoro, 2023)
Introduction: Per- and poly-fluoroalkyl substances (PFASs) are a large, complex group of synthetic chemicals humans can be exposed to from occupational or environmental sources. In this systematic review and meta-analysis, we examined the association between PFAS exposure, particularly Perfluorooctanoic Acid (PFOA), and Perfluorooctane Sulfonic Acid (PFOS), and risk of kidney, liver, and testicular cancer. Methods: We systematically searched PubMed to identify cohort and case-control studies reported after the Monograph of the International Agency for Research on Cancer and the Toxicological Profile of the Agency for Toxic Substances and Disease Registry. We assessed the quality of the studies by using a modified version of the Newcastle-Ottawa Scale (NOS). Forest relative risk (RR) plots were constructed for liver, kidney, and testicular cancer. We conducted stratified analyses by geographic region, study design, quality score, outcome, years of publication, exposure source, and PFAS type. A random-effects model was used to address heterogeneity between studies. Results: Fifteen studies, including ten cohort studies, three case-control studies nested in a cohort, and two case-control studies were included after removing duplicate and irrelevant reports. We found an association between overall PFAS exposure and the risk of kidney cancers (RR=1.18, 95% CI =1.05-1.32; I =52.8%, 11 studies). Also, we showed an association between high-level exposure to PFAS and kidney cancer (RR=1.74, 95% CI =1.23-2.47; p=0.005) and testicular cancer (RR=2.22, 95% CI =1.12-4.39; p=0.057). There was no association with liver cancer. We found no heterogeneity by geographical region, PFAS type, study design, outcome, quality score, year of publication, or exposure source. Only two studies reported results among women. Conclusions: We detected an association between overall PFAS exposure and kidney cancer and high doses of PFAS with testicular cancer. However, bias and confounding cannot be excluded, precluding a conclusion in terms of causality.